Contextualizing the embodied information practices of the devotees of Apung Lucia's Kuraldal - Espiritu, Anna Divine D.; Obille, Kathleen Lourdes B.; Golfo-Barcelona, Mary Grace P.; Buenrostro-Cabbab, Iyra S.; Dar Juan, Elijah John F.; Apolinario, Rhea Rowena U. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2024)
The Kuraldal festival is an enduring celebration in Sasmuan, Pampanga, and is known to be the oldest and longest-running event dating back to the Hispanic era. The festival's essence revolves around the miraculous nature of Apu Lucia, where devotees venerate her for her ability to grant prayers. This resonated deeply with me, who has this genuine interest in this kind of festivities and yearns for blessings. My newfound experiences and curiosities from participating in the Kuraldal led to this academic pursuit. The study aimed to contextualize the embodied information practices of the devotees by exploring their experiences and recollections. They are the missing link between the past and present, given the scarcity of historical records. To provide a more thorough knowledge of this cultural phenomenon, the study contextualizes the embodied information activities within the community. Purposive sampling is used to identify important informants who are actively involved in the festival's organization.

Six devotees, mostly female, ages 39 to 94, who had close ties to the festival, were selected for the study. Semi-structured interviews were held to obtain a thorough understanding of the cultural practices connected to the Kuraldal. Six overarching themes, including ritual components, historical and cultural background, societal perception, and generational shifts, were discovered.

The themes revealed a profound understanding of the festival's cultural significance, its social influences, and its contribution to cultural knowledge within the community. The Kuraldal symbolizes deep-rooted faith, shared values, and the transmission of tradition across generations. However, the study highlights the impact of generational shifts on the festival's practices, suggesting a delicate balance between preserving tradition and adapting to evolving cultural dynamics.

The research concludes that the Kuraldal festival represents not only a cultural event but a living testament to the power of tradition, community, and the preservation of cultural heritage. Recommendations include promoting active community involvement, cultural education for younger generations, and further documentation to ensure the festival's continuity and protection for future generations. The study calls for ongoing research in cross-disciplinary studies to explore the festival from diverse perspectives, contributing to a more holistic understanding.
Thesis
Keywords: Festivals -- Religious aspects -- Philippines; Festivals -- Philippines -- Pampanga; Pampanga (Philippines) -- History